Nutritional ergogenic aids usage and nutritional knowledge in elite female volleyball players - Karabudak, E.; Kin-Isler, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Recently, an increasing use of nutritional ergogenic aids has been observed in various sports, particularly among elite athletes (Ronsen, et al., 1999). Without much scientific backing, a host of dietary supplements have lately been introduced to fill the proposed "micronutrient gap" between the daily requirements and the actual dietary intake, targeting both the general population and specific athletic groups (Rosenbloom et al.,2002). Therefore, the aim of this study was to examine nutritional ergogenic aids usage and nutritional knowledge among elite female volleyball players. Methods Sixty seven volunteer elite female volleyball players, age 15-33 (mean 23.1 ±3.96 years) were included in this study. The instrument was a questionnaire designed to assess nutritional knowledge of athletes. We developed the instrument using selected questions from questionnaires created by Zawila et al (2003). Thus, the entire questionnaire contained 78 questions and was scored in a true/false manner. The questionnaire content consisted of the following: hydration status, macronutrients, vitamins and minerals food variety and groups, relation to food and health, nutrition training, body composition. Athletes were given another questionnaire including question about use of nutritional ergogenic aids. For 2-group comparisons, independent t test were used to identify evidence of a significant difference. Results Use of supplements was widespread with 56.7 % of volleyball players declaring supplement use. None of the volleyball players gave correct responses to the whole total nutrition knowledge (38-60 point, min-max) and subgroups questions except for hydration questions. The mean total nutrition knowledge score of athletes who usage supplement and who don`t usage supplement were 51.5 ±5.47 and 50.5±4.84 points, respectively (mean ± SD). No significant difference was observed between the mean total nutrition knowledge score and their subgroups score of both groups. Discussion Although the results of this study reflect the knowledge of elite female volleyball players and cannot be generalized to all athletes, they indicate that nutritional knowledge may not have an effect on athletes supplement usage. Athletes are exposed to nutrition information from multiple sources, and dietetics professionals are in a position to provide accurate and timely information on a variety of topics of interest to athletes (Ronsen, et al., 1999). Results from this survey suggest that athletes could benefit from learning how supplements affect performance and should be cautioned that supplements cannot make up for a poor-quality diet. References Ronsen, O., Sundgot-Borgen, J., Maehlum, S. (1999). Scand J med Sci sports.9;28-35. Rosenbloom, CA., Johnlagadda, S., Skinner, R. (2002). JADA. 102(3);418-20. Zawila, LG., Steib, CSM., Hoogenboom, B. (2003) J Athletic Training. 38(1);67-74.